PVC Saddle Clamp Feasibility Study - Espinosa, Abigail-Ghene (College of Engineering, 1997)
The name of the product being considered for this study is PVC Saddle Clamp. Saddle Clamps are used to connect the water supply of individual housing units to the water source?s main water pipe. The usual material used for this product is cast iron, but cast iron saddle clamps are prone to corrosion. So a new material, Polyvinyl Chloride, is used to eliminate this problem. The inventor of the product is Mr. Marino Niere, who is also the President and General Manager of Green Horizon Marketing which is currently engaged in the plastic business. Based on the Market Study, the consumers for this product are private realty developers, public housing agencies, and water companies. Only areas in the NCR, and Regions 3 and 4 are considered as initial target. A projected market gap was computed to be 57.074%. As a small-scale enterprise, it wishes to capture only 12% of the total projected demand. It was also determined that door-to-door selling, print advertising and participation in exhibits will be utilized as the marketing strategy for the product. From the Technical Study, the product?s raw materials are available locally. The mode of production was determined using capacity planning and aggregate planning and the results showed that the best mode of production was to produce what is needed and use overtime when necessary. It was also through capacity and aggregate planning that the number of machines needed was determined. From here the plant size was estimated to be 400 to 500 square meters and a recommended site is located at 14 Baner Ave., Fourth Estate Subdivision, Sucat, Paranaque, Metro Manila. The total cost needed for the business? first year of operation was estimated to be P7,693,208.13. In the Financial Study, it was determined that the total project cost will be obtained through a loan from the Development Bank of the Philippines. The cash requirements, profitability and cash flows were computed. It was estimated that the business will have an average Annual Net Income of P3,313,636.73 for five years. The payback period is 2.43 years. The project?s Net Present Value is P2,746,124.89 and the Internal Rate of Return is 29.59%, way above the Minimum Acceptable Rate of Return of 15%. From the Organization and Management Study, manpower requirements were generated and an organizational chart for the new venture was established. The total number of personnel that will be employed is 14. Job qualifications and descriptions were also determined by this study. Based on the Social Profitability Analysis, the cost and benefits that society will receive are as follows. The total costs coming from exempted Municipal and Income Taxes amounts to P4,978,455.09. While the benefits are the value of the demand for other goods which amounts to P15,749,403.13, production of 295,089 added goods to the industry, 14 employment opportunities , and total withholding taxes sum up to P1,104,041.98